Pelatihan pendampingan orang tua dalam edukasi gizi dan makanan sehat anak usia dini - Ari Sofia; Vivi Irzalinda; Annisa Yulistia; Devi Nawangsasi; Sugiana Sugiana (INDRA: Jurnal Pengabdian kepada Masyarakat, 2023)
One of the key factors that affects a child's development is their level of  health and nutrition. Health and nutrition are very important because it can support optimal growth and development.  Children need balanced nutrition to stay healthy and have optimal development. The intention of this activity is to educate the public and conduct workshops on the advantages of a healthy diet for kids' growth and development.  The target of this training is mothers who have early childhood (0-8 years) who are in Way Hui Village.  Three steps are taken to resolve a problem, these are; 1) Stage of initial; 2) Stage of implementation; and 3) the last stage.  The evaluation activity is carried out for every stage by collecting and concluding data. The results of the correlation test showed that there were differences in skill abilities before and after the training given to parents. This is evidenced by the difference in the average  pretest score of 48.33 and the average  posttest of 80.33.  By increasing the value of the posttest, It showed that a person's abilities and skills can be developed through existing knowledge and followed up with training that supports improving the expected skills.